Crocin-I Protects Against High-Fat Diet-Induced Obesity via Modulation of Gut Microbiota and Intestinal Inflammation in Mice - Xie, Xiaoxian; Zhang, Mengya; Sun, Lei; Wang, Ting; Zhu, Zhengyan; Shu, Ruonan; Wu, Fengchun; Li, Zezhi (Frontiers in Pharmacology, 2022)
Crocin-I can regulate physiological changes in the human body by altering inflammation and microbial composition. Gut microbiota is also involved in modulating the pathophysiology of obesity. However, crocin-I’s effect on obesity, and the mechanism underlying its effects on gut microbiota and inflammation, remain poorly understood. Here, high fat diet (HFD) -induced obese mice were administrated crocin-I (20 mg/kg/day) for ten weeks using an oral gavage (HFD-C20 group). HFD-C20, HFD, and Normal chow (NC) groups were compared. The fat content, colon tissue inflammatory cytokine levels, gut microbiota, and short-chain fatty acid (SCFA) levels were measured. Crocin-I reduced body weight and liver weight, and improved glucose resistance in HFD-induced mice. We also found that crocin-I significantly decreased lipid accumulation in the liver. Strikingly, crocin-I alleviated intestinal microbial disorders, decreased the F/B ratio, and decreased the abundance of Proteobacteria in HFD-induced mice. Crocin-I also rescued reduced fecal SCFA levels and repaired altered intestinal barrier functioning and intestinal inflammation in HFD-induced obese mice. These findings indicate that crocin-I may inhibit obesity by modulating the composition of gut microbiota and intestinal inflammation.